2016
DOI: 10.1002/jcc.24264
|View full text |Cite|
|
Sign up to set email alerts
|

Competition between hydrogen and halogen bonding in halogenated 1‐methyluracil: Water systems

Abstract: The competition between hydrogen‐ and halogen‐bonding interactions in complexes of 5‐halogenated 1‐methyluracil (XmU; X = F, Cl, Br, I, or At) with one or two water molecules in the binding region between C5‐X and C4O4 is investigated with M06‐2X/6‐31+G(d). In the singly‐hydrated systems, the water molecule forms a hydrogen bond with C4O4 for all halogens, whereas structures with a halogen bond between the water oxygen and C5‐X exist only for X = Br, I, and At. Structures with two waters forming a bridge bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 46 publications
2
39
0
Order By: Relevance
“…As such, the A•••HD motif is said to be directional when the angle formed by the three atoms A, H, and D (∠A•••HD) lies in the range 160–180° . In addition, there are discussions in the literature that suggest intermolecular interactions with the angles of approach in the 140–160° range can be regarded as the consequence of directional bonding . For CH 3 NH 3 PbI 3 , the ∠I•••HN (or the ∠I•••HC) formed by the three atoms I, H, and N (or I, H, and C) defines the directionality of hydrogen bonding.…”
Section: Resultsmentioning
confidence: 99%
“…As such, the A•••HD motif is said to be directional when the angle formed by the three atoms A, H, and D (∠A•••HD) lies in the range 160–180° . In addition, there are discussions in the literature that suggest intermolecular interactions with the angles of approach in the 140–160° range can be regarded as the consequence of directional bonding . For CH 3 NH 3 PbI 3 , the ∠I•••HN (or the ∠I•••HC) formed by the three atoms I, H, and N (or I, H, and C) defines the directionality of hydrogen bonding.…”
Section: Resultsmentioning
confidence: 99%
“…For iodine and astatine the aug‐cc‐pVDZ‐PP basis with corresponding relativistic effective core potential was employed, whereas all other atoms employed the 6‐31+G(d) basis set. This level of theory was chosen to facilitate comparison with our previous work on XmU‐H 2 O and XmU‐(H 2 O) 2 . In addition, the M06‐2X functional was found to be one of the best functionals for dissociation energies and geometries of X‐bonded dimers .…”
Section: Methodsmentioning
confidence: 99%
“…Because the σ‐hole is located along the extension of the YX bond, halogen bonds are highly directional with halogen‐bond angles typically very close to 180°. However, it has been shown that significantly non‐linear halogen bonds (with halogen‐bond angles 150°–160°) can occur, particularly in complex environments with competing interactions . The strength of halogen bonds is usually found to increase as the halogen group is descended .…”
Section: Introductionmentioning
confidence: 99%
“…bonding interactions in complexes of 5-halogenated 1-methyluracil with one or two water molecules in the binding region between C4-X and C5=O6 (with X = F, Cl, Br, I or At) 22 see Figure 1, note in the previous paper we used a different atom numbering scheme C5-X ≡ C4-X and C4=O4 ≡ C5=O6. In the singly-hydrated systems, the water molecule was found to form a hydrogen bond with C5=O6 for all halogens; however, structures with a halogen bond between the water oxygen and C4-X were only found for X = Br, I and At.…”
mentioning
confidence: 99%
“…Relaxed scans were created by varying the C4-X---O16(water) angle in steps of 1°, while all other geometrical parameters were freely optimized, see respectively. Note that the atom numbering scheme in sub- figure (a-b) differs from that used in the previous Using QTAIM to complement a previous energy-based approach 22 , we investigated the hydrogen and halogen bonding in the region between the C4-X/C4--X BCP and the C5--O6 BCP and associated bond-paths in the 5- …”
mentioning
confidence: 99%